2015
DOI: 10.3758/s13421-015-0531-5
|View full text |Cite
|
Sign up to set email alerts
|

The speed of our mental soundtracks: Tracking the tempo of involuntary musical imagery in everyday life

Abstract: The study of spontaneous and everyday cognitions is an area of rapidly growing interest. One of the most ubiquitous forms of spontaneous cognition is involuntary musical imagery (INMI), the involuntarily retrieved and repetitive mental replay of music. The present study introduced a novel method for capturing temporal features of INMI within a naturalistic setting. This method allowed for the investigation of two questions of interest to INMI researchers in a more objective way than previously possible, concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 53 publications
5
62
0
1
Order By: Relevance
“…Tunes that were more likely to become INMI were generally faster in tempo than non-INMI tunes, although this predictor was only marginally significant in the logistic regression analysis. Future research could investigate the related question of whether tunes from tempo ranges that are more easily entrained to are more likely to become INMI, particularly considering that a large proportion of INMI episodes reported by participants in previous diary studies occurred during repetitive movements, such as walking or running (Jakubowski et al, 2015). assume fairly arch-shaped phrases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tunes that were more likely to become INMI were generally faster in tempo than non-INMI tunes, although this predictor was only marginally significant in the logistic regression analysis. Future research could investigate the related question of whether tunes from tempo ranges that are more easily entrained to are more likely to become INMI, particularly considering that a large proportion of INMI episodes reported by participants in previous diary studies occurred during repetitive movements, such as walking or running (Jakubowski et al, 2015). assume fairly arch-shaped phrases.…”
Section: Discussionmentioning
confidence: 99%
“…Lab-based studies have found that the song that has been heard aloud most recently is more likely to become INMI than a song heard less recently (Hyman et al, 2013;Liikkanen, 2012b), and recent exposure to a tune is generally the most frequently reported trigger of INMI experiences in diary and questionnaire studies (Bailes, 2015;Floridou & Müllensiefen, 2015;Hemming, 2009;Jakubowski, Farrugia, Halpern, Sankarpandi, & Stewart, 2015;. Familiarity can also increase the likelihood that a song will become INMI.…”
Section: Related Previous Research On Inmimentioning
confidence: 99%
“…This study aimed to fill this gap in the literature by examining naturally occurring MEAMs in situ using a diary method. Although similar methodologies have been employed in research on everyday music listening (e.g., North et al, 2004;Sloboda et al, 2001), musical imagery (e.g., Bailes, 2007Bailes, , 2006Jakubowski et al, 2015), and other aspects of autobiographical memory (e.g., Berntsen & Hall, 2004;Schlagman & Kvavilashvili, 2008), the present work represents the first attempt to capture MEAMs in everyday life.…”
mentioning
confidence: 99%
“…Lastly, it may be that there is a ''musicality'' aspect to the TAE. Particular songs are associated with particular tempos, or optimal tempos (Boltz, 2017;Halpern, 1988;Jakubowski et al, 2015;Levitin & Cook, 1996), and this may have increased participants' sensitivity to the altered tempos used in Experiments 1 and 2, though we note that the range of tempos used in the experiments was determined in large part upon the tempos that are characteristic of the R&B and Disco musical genres. To the extent that the stimuli used in Experiment 3 are musically ''generic'' (i.e., these are drumming patterns that are used across a range of popular musical styles and at a wide range of tempos), there is less sensitivity to their appearance(s) at different BPM rates.…”
Section: Discussionmentioning
confidence: 96%
“…The time-shifted stimuli, however, did present a conflict between absolute and relative judgments, as the robust memory for the tempo of these musically rich stimuli provided a basis for a relative judgment, but rather than more accurate responses relative to the scale, those responses were exaggeratedwhich is to say, sharpened. The TAE-as-a-form-ofperceptual-sharpening makes sense both in terms of our having robust, high-level object representations of music (as evidenced by the accuracy of our memories for pitch and tempo, e.g., Jakubowski, Farrugia, Halpern, Sankarpandi, & Stewart, 2015;Levitin & Cook 1996), and in characterizing tempo as a low-level feature of our auditory perception. Drawing on the work of James and Stein (1961), Stewart, Brown, and Chater (2005) have shown that, relative to a central anchoring value (the grand mean of all of the observations), in a relative judgment task optimal criteria tend to be displaced outward toward the extremes.…”
Section: Discussionmentioning
confidence: 99%